Unique Host Iron Utilization Mechanisms of Helicobacter pylori Revealed with Iron-Deficient Chemically Defined Media - Senkovich, Olga (American Society for Microbiology (ASM), 2010)
Helicobacter pylori chronically infects the gastric mucosa, where it can be found free in mucus, attached to cells, and intracellularly. H. pylori requires iron for growth, but the sources of iron used in vivo are unclear. In previous studies, the inability to culture H. pylori without serum made it difficult to determine which host iron sources might be used by H. pylori. Using iron-deficient, chemically defined medium, we determined that H. pylori can bind and extract iron from hemoglobin, transferrin, and lactoferrin. H. pylori can use both bovine and human versions of both lactoferrin and transferrin, contrary to previous reports. Unlike other pathogens, H. pylori preferentially binds the iron-free forms of transferrin and lactoferrin, which limits its ability to extract iron from normal serum, which is not iron saturated. This novel strategy may have evolved to permit limited growth in host tissue during persistent colonization while excessive injury or iron depletion is prevented.